Possibilities of establishing a smallholder pig identification and traceability system in Kenya - Mutua, Florence K.; Lindahl, Johanna F.; Grace, Delia (Springer, 2020)
Consumers have a right to safer foods, and traceability is one approach to meeting their expectations. Kenya does not have an operational animal traceability system, and while a few initiatives have been piloted, these have only focused on the beef value chain. In this paper, we begin a discussion on traceability in the pig value chain, with an initial focus on smallholder systems of Western Kenya. First, a background to local pig production is given, and a description of animal identification and traceability options applicable to these systems is explained. Based on this, a “butcher-to-farm” traceability system, with health, production and food safety as objectives, is discussed. Requirements for establishing such a system (including actor incentives) are additionally discussed. The proposed approach can be piloted in the field and findings used to inform the design of a larger pilot and possibly pave way for implementation of a national traceability system, in line with the guidelines provided by the World Organization for Animal Health (OIE). Organized systems in the area (including commercial producer and trader groups) would offer a useful starting point.